Mitochondrial genomes of two Polydora (Spionidae) species provide further evidence that mitochondrial architecture in the Sedentaria (Annelida) is not conserved - Lingtong Ye (Nature Portfolio, 2021)
Abstract Contrary to the early evidence, which indicated that the mitochondrial architecture in one of the two major annelida clades, Sedentaria, is relatively conserved, a handful of relatively recent studies found evidence that some species exhibit elevated rates of mitochondrial architecture evolution. We sequenced complete mitogenomes belonging to two congeneric shell-boring Spionidae species that cause considerable economic losses in the commercial marine mollusk aquaculture: Polydora brevipalpa and Polydora websteri. The two mitogenomes exhibited very similar architecture. In comparison to other sedentarians, they exhibited some standard features, including all genes encoded on the same strand, uncommon but not unique duplicated trnM gene, as well as a number of unique features. Their comparatively large size (17,673 bp) can be attributed to four non-coding regions larger than 500 bp. We identified an unusually large (putative) overlap of 14 bases between nad2 and cox1 genes in both species. Importantly, the two species exhibited completely rearranged gene orders in comparison to all other available mitogenomes. Along with Serpulidae and Sabellidae, Polydora is the third identified sedentarian lineage that exhibits disproportionally elevated rates of mitogenomic architecture rearrangements. Selection analyses indicate that these three lineages also exhibited relaxed purifying selection pressures.